Disordered Regions Flanking the Binding Interface Modulate Affinity between CBP and NCOA. Issue 13 (15th July 2022) - Karlsson, Elin; Schnatwinkel, Jan; Paissoni, Cristina; Andersson, Eva; Herrmann, Christian; Camilloni, Carlo; Jemth, Per
Graphical abstract: Highlights: The role of disordered flanking regions in protein interactions is poorly understood. Disordered flanks of CID from ACTR increase the affinity for NCBD from CBP. The flanking regions likely make non-specific hydrophobic interactions with NCBD. Disordered flanking regions might generally modulate affinity in protein interactions. Abstract: Recognition motifs that mediate protein–protein interactions are usually embedded within longer intrinsically disordered regions. While binding interfaces involving the recognition motif in such interactions are well studied, less is known about the role of disordered regions flanking the motifs. The interaction between the transcriptional co-activators NCOA3 (ACTR) and CBP is mediated by coupled binding and folding of the two domains CID and NCBD. Here, we used circular dichroism and kinetics to directly quantify the contribution of the adjacent flanking regions of CID to its interaction with NCBD. Using N- and C-terminal combinatorial variants we found that the flanking regions promote binding in an additive fashion while retaining a large degree of disorder in the complex. Experiments at different ionic strengths demonstrated that the increase in affinity is not mediated by electrostatic interactions from the flanking regions. Instead, site-directed mutagenesis and molecular dynamics simulations suggest that binding is promoted by short-lived non-specific hydrophobic contacts between the flanking regions and NCBD. Our findings are consistent with highly frustrated interactions outside of the canonical binding interface resulting in a slightly energetically favorable fuzzy binding. Modulation of affinity via flanking regions could represent a general mechanism for functional regulation by intrinsically disordered protein regions.